What Arthroscopic Skills Need to Be Trained Before Continuing Safe Training in the Operating Room? - Tuijthof, Gabrielle; Cabitza, Federico; Ragone, Vincenza; Compagnoni, Riccardo; Dutch Arthrocopy Society Teaching Committee; Randelli, Pietro (The Journal of Knee Surgery, 2017)
The purpose of this study was to generate consensus among experienced surgeons on “what skills a resident should possess before continuing safe training in the operating room (OR).” An online survey of 65 questions was developed and distributed to surgeons in the European community. A total of 216 responded. The survey included 15 questions regarding generic and specific skills; 16 on patient and tissue manipulation, 11 on knowledge of pathology and 6 on inspection of e-anatomical structures; 5 methods to prepare residents; and 12 on specific skills exercises. The importance of each question (arthroscopic skill) was evaluated ranging from 1 (not important at all) to 6 (very important). Chi-square test, respondent agreement, and a qualitative ranking method were determined to identify the top ranked skills (p < 0.05). The top four of general skills considered important were “anatomical knowledge,” “tissue manipulation,” “spatial perception,” and “triangulation” (all chi-square test > 134, p < 0.001, all excellent agreement > 0.85, and all “high priority” level). The top ranked 2 specific arthroscopic skills were “portal placement” and “triangulating the tip of the probe with a 30-degree scope” (chi-square test > 176, p < 0.001, excellent agreement, and assigned high priority). The online survey identified consensus on skills that are considered important for a trainee to possess before continuing training in the OR. Compared with the Canadian colleagues, the European arthroscopy community demonstrated similar ranking.
Keywords: arthroscopy; skills; survey; opinion